Remarks on the approximation of a M|G|∞ queue system by a Markov renewal process - Ferreira, Manuel Alberto M. (2014)
It is presented a Markov renewal process, suggested in (1, 2) as a tool to obtain good approximations for the M|G|∞ queue interesting parameters.